The GCP Event Experiment: Design, Analytical Methods, Results - BANCEL, PETER; NELSON, ROGER (Journal of Scientific Exploration, 2010)
Studies of anomalous correlations between mind and matter usually focus on participating subjects and isolated target systems. We report on a decade-long experiment which finds that anomalous mind-matter correlations may be a pervasive aspect of reality. The Global Consciousness Project (GCP) measures the output deviation of a global network of physical random number generators (RNGs) at the time of major world events. The project hypothesizes that the coherent attention or emotional response of large populations induced by the events will correspond to characteristic deviations of the network output. We describe the motivation and scope of the experiment and the analytical procedures employed to test the hypothesis, and present the results of 236 events accumulated over the first 9 years of operation. The cumulative significance across all events favors the hypothesis by more than 4.5 standard deviations. Beyond a test of the basic hypothesis, secondary analyses show that the result is driven by correlations in the RNG network across global distances. Keywords: random numbers—REG—RNG—anomalies—global consciousness— consciousness—parapsychology—mind-matter interaction